(untitled) (GYMNASIUM, 2009)
This paper tries to highlight the need to develop specific means of action for individual physical preparation of players specializing as an extreme and their planning methodology, in the teams secondary representative that can easily be adapted by any coach without affect objectives. Aspects of individuality in the preparation of players can be seen from another angle, namely, for those who evolve extreme position, individualization may know and nuances of individuality in couples of players or groups of players in similar conditions and identical to those of the competition.